KUALITAS PENGUNGKAPAN EMISI KARBON SEBAGAI MEDIASI ANTARA KEPEMILIKAN PENGENDALI DAN NILAI PERUSAHAAN - Tamariska Militia Lasapu; I Putu Sugiartha Sanjaya (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Sustainability and environmental responsibility have become global concerns, including in Indonesia, which ranks among the ten largest greenhouse gas emitters worldwide. Efforts to reduce carbon emissions are being strengthened through various policies such as the Paris Agreement, the Financial Services Authority Regulation (OJK) No. 51/POJK.03/2017 on Sustainable Finance, and the implementation of carbon tax and trading schemes. In the context of corporate governance, the role of controlling shareholders can influence the direction and quality of environmental information disclosure, including carbon emissions, and ultimately affect firm value. Controlling shareholders with greater control rights than cash flow rights may make decisions that do not always align with minority shareholders’ interests, potentially reducing firm value. This study examines the effect of controlling shareholders’ cash flow right leverage (CFRL) on firm value, with the quality of carbon emission disclosure as a mediating variable. The research focuses on the banking sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with 225 firm-year observations and a 10% ownership cutoff for identifying controlling shareholders. Hypothesis testing was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS software. The results show that CFRL has a significant negative effect on both carbon emission disclosure quality and firm value. Furthermore, carbon emission disclosure quality significantly mediates the relationship between CFRL and firm value in a positive direction.